Holy War and a Place in Paradise? Development of the East Roman Holy War from the 4th until the 11th century - SYVÄNNE, Ilkka (Historia i Świat, 2020)
The article analyses the development of the holy war in East Rome from its beginning until the 11th century. The article takes the stance that it is meaningless what the official religious doctrine was when the soldiers themselves believed and followed the doctrine of holy war which promised a place in heaven for all fallen soldiers.